The Somali Anti-Piracy Campaign, 2008-2012 - Justus Ondigi; Kenneth Ombongi; George Gona (Journal of BRICS Studies)
Sea piracy, a centuries old practice, has been portrayed as a phenomenon that rewards its perpetrators while decaying the states where it thrives. Fueled by its unsustainable criminal economies that erode and weaken the fibre of the state, the deterioration has over the centuries and millennia prompted states to inconclusively counter the menace. This fight against piracy has been a teeter-totter of sorts whose common thread has been the rise, decline and recurrence of piracy throughout history. Yet, despite this incongruous reality, states have continued to roll out strategies with hopes of ending piratical vagaries and reforming its attendant criminal economies. While anti-piracy interventions of yore abound, their descriptions have not attracted deserving scholarly scrutiny, an aberration that can be redeemed by contextualizing initiatives taken to curb the fabled Somali piracy. This article interrogates the international, regional and national Somali anti-piracy strategies whose deficiencies shed light on why piracy remains a recurring scourge. Capitalizing on Somalia’s instability and location, the article identifies the intricacies of the selfish considerations that underlie leading world powers and regional agencies ‘humanitarian’ decision to join the Somali anti-piracy campaign.